PERAN LURAH DALAM PEMILIHAN UMUM LEGISLATIF, PEMILIHAN UMUM PRESIDEN/WAKIL PRESIDEN, DAN PEMILIHAN KEPALA DAERAH/WAKIL KEPALA DAERAH DI KOTA TEBING TINGGI - Hatta Ridho (PERSPEKTIF, 2016)
This research intended to know and describe the role of village chief according to regulations and laws regulating the performance of legislatif election, president election, and major election, using the qualitative method with technique of collecting data, depth interview and analysis of document. The key informan in this research is individual who knows of involved directly in process of general election and major election, i.e., villages chief, members of KPUD, legislatures, people figures, election monitor and to have functionaries of political party.The results of research indicates that village chief has strategic role in three momentums of election. Village chief as facilitator of election is involved in technique support in socialization process, logistic administration, recruitment of PPS and secretariat of PPS, and facilitaty of PPS office. The subject of debate is neutrality of village chief and his apparatus in one of election momentum, i.e., major election. This is caused by between that candidates of Major, two of them are incumbent who is holding the position and to have structure relation with village chief.